Risk factors for a high Comprehensive Complication Index score after major hepatectomy for biliary cancer: a study of 229 patients at a single institution. Issue 9 (September 2016) - Nakanishi, Yoshitsugu; Tsuchikawa, Takahiro; Okamura, Keisuke; Nakamura, Toru; Tamoto, Eiji; Noji, Takehiro; Asano, Toshimichi; Amano, Toraji; Shichinohe, Toshiaki; Hirano, Satoshi
Abstract: Background: The Comprehensive Complication Index (CCI) is a new tool to evaluate the postoperative condition by calculating the sum of all complications weighted by their severity. The aim of this study was to identify independent risk factors for a high CCI score (≥40) in 229 patients after major hepatectomies with biliary reconstruction for biliary cancers. Methods: The CCI was calculated online viawww.assessurgery.com . Independent risk factors were identified by multivariable analysis. Results: 57 (25%) patients were classified as having CCI ≥ 40. On multivariable analysis, volume of intraoperative blood loss (≥2.5 L) (p = 0.004) and combined pancreatoduodenectomy (PD) (p = 0.006) were independent risk factors for CCI ≥ 40. A high level of maximum serum total bilirubin was identified as independent risk factors for a high volume of intraoperative blood loss. Liver failure (p = 0.046) was more frequent in patients with combined PD than in those without. Discussion: Patients who undergo preoperative external biliary drainage for severe jaundice might have impaired production of coagulation factors. When blood loss during liver transection becomes difficult to control, surgeons should consider various strategies, such as second-stage biliary or pancreatic reconstruction. In patients planned to undergo major hepatectomy with combined PD, preoperative portal vein embolization is mandatory to prevent postoperative liver failure.